The Addition Effect of Chitosan and Bacillus amyloliquefanciens Bacteria in the Tapioca Liquid Waste Phytoremediation Process - Febriningrum, Panca Nugrahini; M. Nur, Mela Sari (Universitas Negeri Semarang, 2021)
Tapioca liquid waste treatment using phytoremediation process of water hyacinth plant has not reached the maximum result, therefore it is necessary to give more treatment by adding chitosan as a pretreatment and Bacillus amyloliquefanciens bacteria. This study aims to determine and determine the effect of the addition of chitosan and bacteria to increase the ability of water hyacinth plants in phytoremediation of tapioca wastewater. The research process was carried out in two stages of tapioca liquid waste processing, namely the batch and continue stages. The batch process uses a reactor and the continuous process uses three reactors connected in series for each treatment. The result in the batch process without the addition of bacteria without the addition of bacteria namely, COD removal of 79%, TSS removal of 65,12%, VSS removal of 60% and final pH of 6,9 for 12 days with variation of chitosan 25 mg/l. In the treatment of the addition of large bacteria, COD removal was 81,78%, TSS removal 86,11%, VSS removal was 89,66% and final pH was 6,8 for 8 days with a variation of chitosan 50mg/l. The results in the continued process with a residence time of 12 hours COD removal of 78,25% with an end value of TSS 400 mg/l, VSS 200 mg/l and pH 5,5. So it can be concluded that the effect of the chitosan and bacteria on the phytoremediation process of tapioca wastewater namely, the more chitosan is added, the COD removal is smaller and the pH value tends to be constant, but the VSS and TSS removal is greater in the treatment without bacteria. The treatment with the addition of bacteria showed that the more chitosan was added, the greater the COD removal and TSS removal. This is in contrast to the VSS removal which is getting smaller, while the pH value tends to be constant.